The Impact of Purple Sweet Potato Flour Substitution on the Physical and Organoleptic Characteristics of Non-flaky Crackers - Yudiastuti, Silvia Oktavia Nur; Purnama, Wiwin; Halim, Abdul (P3M Politeknik Negeri Jember, 2025)
Non-flaky crackers are snacks like biscuits but go through a fermentation process and are not layered. This research aimed to determine the effect of purple sweet potato flour substitution on non-flaky crackers' physical and organoleptic characteristics. This research used a Completely Randomized Design (CRD) method consisting of six treatments and three replications. The treatments are C0 (100% wheat flour), C1 (10% purple sweet potato flour, 90% wheat flour), C2 (30% purple sweet potato flour, 70% wheat flour), C3 (50% purple sweet potato flour, 50% wheat flour). wheat), C4 (70% purple sweet potato flour, 30% wheat flour), C5 (90% purple sweet potato flour, 10% wheat flour). Data analysis used the Microsoft Excel 2010 program, the ANOVA (Analysis of Variance) method, then continued with data processing using IBM SPSS Statistics 25 and continued with Duncan's Multiple Range Test. The research showed that substituting purple sweet potato flour had significantly affected the characteristics and hedonic colour, texture, physical characteristics, and characteristics of cracker products. The best treatment was the C4 iteration of 70% purple sweet potato flour and 30% wheat flour.